2010
DOI: 10.1371/journal.pone.0014141
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Dengue Virus in Mayotte, Indian Ocean, 2006

Abstract: BackgroundAlthough Dengue virus (DENV) circulation had been documented in neighbouring South-western Indian Ocean Islands, its presence in Mayotte is poorly characterised. To address this issue, we aimed to assess the seroprevalence of dengue IgG antibodies (DENV-IgG Ab) among the population and to investigate potential associations with individual and household characteristics.Methods/Principal FindingsIn November–December 2006 we conducted a cross-sectional serologic survey in Mayotte among 1,154 inhabitants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
(27 reference statements)
3
8
0
Order By: Relevance
“…Sera were most frequently reactive with DENV1 and DENV3 and less frequently with DENV2 and DENV4. These results are in keeping with the history of dengue epidemics on the archipelago during the last seventy years: DENV1 epidemics was recorded in 1948 and 1993, DENV2 in 1984 [20] and DENV3 in 2010 [21] To our knowledge, serotype 4 has never been reported as causing an epidemic in the Indian Ocean region though some uncertainty remains with regard to serotypes that have been circulating during the 1948 and 1984 epidemics in Comoros [22]. Yet, neutralizing antibodies to DENV4 were detected in the present series in over half of titrated sera (44/78).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Sera were most frequently reactive with DENV1 and DENV3 and less frequently with DENV2 and DENV4. These results are in keeping with the history of dengue epidemics on the archipelago during the last seventy years: DENV1 epidemics was recorded in 1948 and 1993, DENV2 in 1984 [20] and DENV3 in 2010 [21] To our knowledge, serotype 4 has never been reported as causing an epidemic in the Indian Ocean region though some uncertainty remains with regard to serotypes that have been circulating during the 1948 and 1984 epidemics in Comoros [22]. Yet, neutralizing antibodies to DENV4 were detected in the present series in over half of titrated sera (44/78).…”
Section: Discussionsupporting
confidence: 84%
“…In that island, a cross-sectional serologic survey conducted in 2006 during an inter-epidemic period for dengue, showed a rate of DENV-specific IgG antibodies of 22.7% with an age-specific prevalence peaking at 38.8% in the 25–54 years age group while the 2–14 age group was almost completely preserved [20]. Interestingly, Comorian native inhabitants aged 15 years or over, who had immigrated to Mayotte, were around ten-times more affected than individuals of the same age born in Mayotte [20]. …”
Section: Discussionmentioning
confidence: 99%
“…16 In general, studies have shown an increase in seroprevalence with age as a result of a longer period of exposure to the DENV circulating in endemic regions. 17,18,[35][36][37][38] In the localities of Axochiapan and Tepalcingo, the magnitude of seroprevalence detected in this study as well as the presence of dengue cases over the last 5 years situate them in the category of endemic areas in Mexico. Although the incidence is higher in Axochiapan than Tepalcingo, the difference in global seroprevalence between the localities was not statistically significant, but in the adjusted analysis by age and other variables, we observed a small difference that was statistically significant (11%, 95% CI = 5-17) and may be explained by differences in population density (Axochiapan = 0.193 habitants/km 2 ; Tepalcingo = 0.072 habitants/km 2 ).…”
Section: Discussionmentioning
confidence: 98%
“…Second, we aimed to detect symptomatic illness and did not look for asymptomatic infections. Therefore, we likely underestimated the number of people infected during the outbreak given evidence that 3–25% of Chikungunya virus infections are asymptomatic [ 29 , 30 ]. Third, residents may have been unable to reliably recall their symptoms or onset of illness, particularly for milder illnesses, which may have led to an underestimation of suspected cases.…”
Section: Discussionmentioning
confidence: 99%